Interest rate linkages in EMU countries: a rolling threshold vector error-correction approach - Tigran Poghosyan; Jakob de Haan; Tor Helge Holmås (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper revisits financial market integration in the European Economic and Monetary Union, using a threshold vector error-correction model (TVECM) for a fixed rolling window. This approach enables us to analyze the dynamics of transaction costs and detect any co-movements with (policy induced) changes in the financial environment. The TVECM methodology is applied on interest rates from different financial markets (government bonds, deposits, loans and mortgages) in Germany, France, Italy, Belgium and the Netherlands for the 1980-2006 period. Our main finding is that only for some country pairs and financial market segments there is evidence in support of financial integration.
Keywords: E43; F36; 330; Zinsparität; Internationaler Finanzmarkt; Marktintegration; Fehlerkorrekturmodell; Schätzung; EU-Staaten